Strongyloidiasis Presenting as Yellowish Nodules in Colonoscopy of an Immunocompetent Patient - Hannah Ra; Jun-Won Chung; Dong Hae Chung; Jung Ho Kim; Yoon Jae Kim; Kyoung Oh Kim; Kwang An Kwon; Dong Kyun Park (Korean Society of Gastrointestinal Endoscopy, 2019)
Strongyloides stercoralis is endemic to tropical and subtropical regions, and infections are usually asymptomatic. However, immunocompromised patients, such as those receiving immunosuppressive therapy, high-dose steroids, or chemotherapy, can develop fatal hyperinfections. An 84-year-old man without any symptoms was diagnosed with strongyloidiasis during a regular screening colonoscopy. His medical history only involved a gastric endoscopic submucosal dissection for early gastric cancer 6 months previously. Few cases have been published about asymptomatic strongyloidiasis diagnosed in an immunocompetent host via endoscopic mucosal resection with characteristic colonoscopic findings. We report a case of colon-involved asymptomatic strongyloidiasis with specific colonic findings of yellowish-white nodules. This finding may be an important marker of S. stercoralis infection, which could prevent hyperinfections.